Risk Management in Sharia Insurance: A Juridical Analysis on Legal Basis and Its Implementation - Nazla Aina Afrinti Telaumbanua; Afri Kartika; Nazwa Salsabila Lubis; Siti Nuraisyah; Muhammad Ali Guntur (Jurnal Cendikia ISNU SU, 2025)
Sharia insurance is basically based on the principle of help-help (ta'āwun) known as at-ta'mīn, takaful, and tazāmun. In contrast to conventional insurance, sharia insurance emphasizes a mechanism of mutual protection through the management of tabarru' funds  and the use of contracts in accordance with sharia principles. In practice, risk management in sharia insurance is not only an operational technical aspect, but also has a normatively binding legal dimension. This research aims to analyze the legal basis and implementation of risk management in sharia insurance from a juridical perspective. The research method used is normative juridical with a literature approach, through the collection of secondary data sourced from laws and regulations, fatwas of the National Sharia Council of the Indonesian Ulema Council, legal literature, and relevant scientific works. The results of the study show that risk management is an important legal instrument to anticipate uncertainty and potential losses that can hinder the achievement of sharia insurance goals. Risk is understood as uncertainty arising from internal and external factors of the institution. The implementation of risk management must be guided by the provisions of the Financial Services Authority and sharia principles to ensure legal compliance, participant protection, and the sustainability of the sharia insurance business.